Monitoring of Tamil Nadu Afforestation Project (TAP) Using Irs Id Satellite Imagery - a Case Study in Jotidnagar Village, Tiruv Annamalai District, Tamil Nadu - Sreedharan, C. K.; Dhanapal, K. (Indian Forester, 2005)
Tamil Nadu Afforestation Project (TAP) was carried out from 1997 onwards to restore the degraded forests, by involving the local villagers abutting such forest areas, based on Joint Forest Management (JFM) concept. The project mainly focuses on improving the forest, hydrological resources and community development. Monitoring the project is vital to assess the long-term sustainability of the resources and thereby to make informed decisions. Among the many criteria and indicators of the project objectives, forest cover improvement would attract the attention of the policy makers. Information about the change is necessary for monitoring the progress of intervention carried out in any project. The paper deals with the forest cover change detection using remotely sensed data obtained before (1998) and after (2002) the intervention of TAP, in Jothinagar village of Tiruvannamalai District in Tamil Nadu State. The results shows that there is an improvement in 35% forest cover in the study area over a period of four years.